2021
DOI: 10.1038/s41598-021-92497-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA in serum is associated with increased mortality risk in hospitalized COVID-19 patients

Abstract: COVID-19 has overloaded national health services worldwide. Thus, early identification of patients at risk of poor outcomes is critical. Our objective was to analyse SARS-CoV-2 RNA detection in serum as a severity biomarker in COVID-19. Retrospective observational study including 193 patients admitted for COVID-19. Detection of SARS-CoV-2 RNA in serum (viremia) was performed with samples collected at 48–72 h of admission by two techniques from Roche and Thermo Fischer Scientific (TFS). Main outcome variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…These efforts were aimed to improve patient stratification and make a better use of the available resources to optimise health care. After several months of intensive research, some prognostic clinical biomarkers have been identified, including lymphocyte count, D-dimer, C reactive protein (CRP), ferritin, Interleukin (IL)-6 or viremia ( 3 , 4 ). Moreover, dysregulation of other cytokines, including IL-2, IL-10, Interferon (IFN)-γ, monocyte chemoattractant protein (MCP)-1 or C-X-C Motif Chemokine Ligand (CXCL)10 in COVID-19 patients have also been reported ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…These efforts were aimed to improve patient stratification and make a better use of the available resources to optimise health care. After several months of intensive research, some prognostic clinical biomarkers have been identified, including lymphocyte count, D-dimer, C reactive protein (CRP), ferritin, Interleukin (IL)-6 or viremia ( 3 , 4 ). Moreover, dysregulation of other cytokines, including IL-2, IL-10, Interferon (IFN)-γ, monocyte chemoattractant protein (MCP)-1 or C-X-C Motif Chemokine Ligand (CXCL)10 in COVID-19 patients have also been reported ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could result in a decreased detection of this human gene target in serum samples. Regardless, previous studies already described detection of SARS-CoV-2 in serum [ 19 ], which could be associated with increased mortality risk in hospitalized COVID-19 patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the virus demonstrates tissue tropism for some organs [16], early reports suggested that most hospitalized patients did not have detectable levels of viral materials in their sera [17]. Although a more recent report has demonstrated viral materials in 50-60% of sera of moderate-to-critically ill patients, no association has yet been shown between serum detection and the development of multiorgan dysfunction syndrome, either prior to admission or during the first 24 h of intensive care [18]. Overall, the evidence suggests that viremia is not a requirement for either symptomatology or severe disease.…”
Section: Hypothesismentioning
confidence: 99%